The Quality Of Rendang Lokan Is Produced From The Use Of Wet And Dry Spices - Ramadani, Desi; Holinesti, Rahmi (Universitas Negeri Padang, 2022)
This research is motivated by the already well-known rendang lokan to various foreign countries with various flavors and various typical spices from Indonesia. Rendang lokan is a lokan that is processed by kneading or cooking on low heat, the lokan used is a medium-sized lokan and is still fresh, so that in the process of processing rendang lokan is not easily crushed when cooked dry. The purpose of this study was to analyze the quality of rendang lokan with wet and dry spices and fern leaves as a supporting material, in terms of color, aroma, texture, and taste of rendang lokan. This type of research is a pure experiment, with the aim of knowing the effect as well as the difference between two different variables. The research design used was a completely randomized design (CRD) by teaching two treatments (X1, X2) with 3 repetitions. The type of data used is primary data obtained directly from 5 expert panelists with a significant level of 5% (= 0.05). The results showed that there was no significant effect on the quality of rendang lokan using both wet and dry spices. With the meaning of the word people outside West Sumatra can use dry spices to process rendang lokan with a distinctive taste of Minang cuisine. From the statement, it can be concluded that the indicators of the quality of color, aroma, texture, and taste Ho are accepted because t count < t table.